LAYOUT DESIGN AND DREDGING WORK OF NAVIGATION CHANNEL AND BASIN IN PELABUHAN RATU STEAM POWER PLANT WEST JAVA PROVINCE - Gunawan Gomasjaya, Vincent
One example of steam power plant in Indonesia is Pelabuhan Ratu Steam Power Plant, Sukabumi, West Java province. Initially, the Pelabuhan Ratu Steam Power Plant dock was designed to receive ships with a capacity of 15,000 DWT. However, this steam power plant plans to increase the ship’s capacity to 35,000 DWT. This ship has a draft of 11 meters. Meanwhile, the depth of the waters in the area is about 7 meters. Therefore, dredging is needed to increase the depth of the water in the area. The designed approach channel has a depth of 13.75 meters, a width of 86 meters, and a slope of 1:5. Meanwhile, the turning basin has a depth of 13.75 meters and diameter of 281 meters. From the results of this design, the estimated volume of dredging is 1,722,966 m3. This dredging work will be carried out using one TSHD Hang Jun 6008 vessel. After calculation of productivity of this TSHD vessel, an estimated duration of 86 days is obtained. Next, the breakwater stability analysis was carried out using Plaxis software. The results of the analysis show that the breakwater is still in a stable state after the dredging process is carried out. This dredging work requires a cost of Rp144.724.781.245.